The Effectiveness of Interactive Presentation Features in Quizizz on Students’ Reading Comprehension of Analytical Exposition Text - Nova Nur Solecha (Retain: Journal of Research in English Language Teaching, 2026)
Many students keep facing difficulties in terms of mastering reading comprehension, especially when learning English as a foreign language. Teaching that relies on a single textbook often leaves students feeling bored and disengaged, which can limit their reading development. This study aims to find out whether the use of Quizizz Interactive Presentation feature as learning media can help high school students to improve their reading comprehension performance, particularly reading analytical exposition text. This study used a quantitative approach with quasi-experimental design. The participants were 70 eleventh grade students from a public high school in East Java. The students were divided into two groups. The experimental group used Quizizz Interactive Presentation feature as the learning media, while the control group used a textbook-based learning as they usually do. Both groups were given a pre-test and post-test to measure their reading comprehension. The results showed that students in the experimental group had slightly higher post-test scores compared to the control group. The difference between the two groups was statistically significant, and the effect size was moderate. This research supports the idea that digital tools can make learning more interesting and effective for students, and lead to better performance. However, this study has some limitations, including the short treatment period and using only one school. Future research could explore a longer treatment period, involve in several schools, use other Quizizz features or combine Quizizz with other digital tools to make the teaching and learning activities much more engaging.